Revisiting the agency conflicts in family owned pyramidal business structures: A case of an emerging market - Muhammad Farhan Basheer; Shuchi Gupta; Rabeeya Raoof; Waeibrorheem Waemustafa (Cogent Economics & Finance, 2021)
The agency problem strikes as an ethical, practical, and economic issue in equal measures. The principal objective of the current research is to trace the nature of the agency conflicts in the family-owned pyramidal business groups of corporate Malaysia and how they affect the firm value. It is argued that the principa͐l-principal (PP) conflict is more severe in family-owned business firms. To achieve the objectives of the current study, the GMM and the fixed effect estimates are used. In addition, to find the difference between family-owned firms and family-owned firms in the pyramidal business, we have employed the Mann-Whitney test. The null hypothesis is accepted which indicates that the impact of the PP conflict among family firms is different from those in pyramidal business groups. The final sample of 420 firms listed on the Bursa Malaysia is chosen for the analysis. The results of the current study provide support to the hypothesized results that the PP conflict is severe in family-owned groups and has a significant effect on firm value. The findings of the current study also provide support that the PP conflict is prevalent in Malaysia, supporting the earlier evidence regarding the expropriation of minority shareholders rights reported in the studies carried out on samples of Malaysian non-financial firms. This is also in line with our measure of PP conflict severity, which is high in pyramidal family firms. Overall, the results provided support to the expropriation hypothesis. Thus, the findings of this study also confirm the view that in family-owned Malaysian firms, the ethical dilemmas of wealth expropriations do exist and are more intense in the pyramidal family-owned business structures. Instead of relying on traditional methods, the current study employed a synthetic measure to gauge the PP conflict. The study which is among the pioneer on the expropriation of minority shareholders will be helpful for policymakers, researchers and finance professionals in understanding the issues related to principal-principal conflict, and firm value in family-owned pyramidal business groups of Malaysia.
Keywords: G3; 330; Agency Theory Pyramidal; Bursa; family firms; Malaysia; Principal-Principal (PP) conflict